Peranan Kepemimpinan dalam Menin Peranan Kepemimpinan dalam Meningkatkan Kinerja Pegawai pada Biro Tata Pemerintahan Sekretariat Daerah Aceh - Dedi Sufriadi (eCo-Buss, 2018)
This study is about the function of leadership in improving the performance of employees at Biro Tata Pemerintahan Sekretariat Daerah Aceh. source collection using two methods, namely library research and field study. Through field study, the researcher performs through two techniques, namely: observation that is the way source collection is done by looking and plunge directly into the routine that happened at it and through interviews, is by conducting interviews with the staff -staff at it. The results of the research found it employed 62 staffs. But the composition of greater of staff than the workload makes unperformances. There are still a number of employees who do not get a job clearly so that it allows them to spend time with activities that are not useful. Then the policy of placement and division of labor that is not done in a proesional also make the performance of employees at this Bureau still needs to be considered. In the midst of the rapidly changing work environment that influences employee's work behavior, Biro Tata Pemerintahan Sekretariat Daerah Aceh needs qualified leaders so that issues related to employee behavior and performance can be resolved.